The Relative Risk and Incidence of Immune Checkpoint Inhibitors Related Pneumonitis in Patients With Advanced Cancer: A Meta-Analysis - Ma, Ke; Lu, Yali; Jiang, Shanshan; Tang, Jiangong; Li, Xin; Zhang, Yuyang (Frontiers in Pharmacology, 2018)
Background: Recently, immune checkpoint inhibitors have been proved one of the most promising anti-cancer therapy, series clinical trials have confirmed their efficacy. But they are also associated with distinctive set of toxic effects, which are recognized as immune-related adverse events. Among those immune-related adverse events, pneumonitis is rare, but it is often clinically serious and potentially life-threatening. Although many clinical trial results of PD-1/PD-L1 inhibitors had been reported incidence of pneumonitis, the knowledge based on the individual cohort data from each clinical trial is limited. So we conducted a meta-analysis of trials of PD-1/PD-L1 inhibitors in patients with advanced cancer and compared relative risk and incidence among different tumor types and therapeutic regimens. Such an analysis may provide important knowledge of this rare but clinically significant and potentially serious immune related adverse event. Methods: Electronic databases were used to search eligible literatures, include randomized controlled trials (RCTs) comparing Immune checkpoint inhibitors vs standard therapies. All-grade (1–4) or high-grade (3–4) pneumonitis events were extracted. The summary relative risk, summary incidence, and 95% conﬁdence intervals were calculated Results: The incidence of all-grade and high-grade pneumonitis in NSCLC was significantly higher compared with other type of tumor (include Melanoma UC HNSCC) (3.1% vs 2.0% p = 0.02, 1.4% vs 0.6% p = 0.03). The risk of all-grade pneumonitis were obtained for all patients in both experimental arm and control arm, treatment with immune checkpoint inhibitors targeting PD-1/PD-L1 did significantly increase the risk of all-grade and high-grade pneumonitis compared with controls (fixed effects, RR: 4.70; 95% CI: 2.81–7.85; p < 0.00001, RR: 3.33; 95% CI: 1.68–6.59; p = 0.0006). Conclusions: The incidence of immune checkpoint inhibitor related pneumonitis was higher in NSCLC than other types of tumor. Patients with immune checkpoint inhibitor in experiment arms are more likely to experience any grade pneumonitis than control arms. These findings suggest that clinician need to draw more attention on this rare but serious adverse event